The night we met [compact disc, unabridged] - Jimenez, Abby (Blackstone Publishing, 2026)
Larissa and Chris are great friends, co-parenting a slightly unhinged rescue Yorkie. But Larissa didn't choose Chris to drive her home after the concert all those months ago. She went with his best friend, and he became her boyfriend. All Chris wants is for Larissa to be happy. Standing by on the sidelines is slowly killing him, but making a move would destroy someone else.